Viral protein apoptin as a molecular tool and therapeutic bullet: implications for cancer control. (September 2007) - Visser, Astrid E; Backendorf, Claude; Noteborn, Mathieu
The chicken anemia virus-derived protein apoptin induces apoptosis in human tumor cells via a p53-independent pathway, while leaving normal cells intact. Moreover, apoptin treatment in preclinical animal studies leads to reduced tumor growth or remission without a detectable effect on healthy tissues. Apoptin is activated by a still unknown tumor-specific kinase activity. The mode of action of apoptin is under intense investigation, as certain features make it a promising tool for discovering early events in tumorigenesis, identifying druggable targets for antitumor treatment and possibly serving as an antitumor therapy in itself.